Motocross versus motorcycle injury patterns: A retrospective National Trauma Databank analysis. Issue 2 (August 2019) - Fierro, Nicole; Inaba, Kenji; Aiolfi, Alberto; Recinos, Gustavo; Benjamin, Elizabeth; Lam, Lydia; Strumwasser, Aaron; Demetriades, Demitrios
Abstract : BACKGROUND: Motocross-related injury patterns and outcomes are poorly understood. The purpose of this analysis was to characterize the epidemiology, injury patterns, and outcomes of motocross collisions. These parameters were compared with motorcycle collisions for context. METHODS: The National Trauma Databank (NTDB) (2007–14) was used to identify and compare injured motorcycle and motocross riders. Variables extracted were demographics, Abbreviated Injury Scale for each body area, Injury Severity Score, and emergency department vital signs. Outcomes included mortality, ventilation days, intensive care unit length of stay, and hospital length of stay. RESULTS: Of the 5, 774, 836 NTDB patients, 141, 529 were involved in motocross or motorcycle collisions (31, 252 motocross and 110, 277 motorcycle). Overall, 94.4% were drivers and 87.4% were male. Motocross riders were younger (23 vs. 42, p < 0.001), more likely to use helmets (68.9% vs. 54.1%, p < 0.001), and less likely to have used alcohol (8.4% vs. 23.0%, p < 0.001). Head and chest injuries were less common in motocross patients (28.6% vs. 37.2%, p < 0.001; 25.5% vs. 37.7%, p < 0.001, respectively), as were Injury Severity Score of greater than 15 and Glasgow Coma Scale of less than or equal to 8 (18.2% vs. 28.1%, p < 0.001; 3.7% vs. 7.7%, p < 0.001, respectively). Overall mortality was significantly lower in the motocross group (0.3% vs. 1.4%, p < 0.001). Stepwise logistic regression analysis identified age of older than 60 years, Glasgow Coma Scale of less than or equal to 8, hypotension on admission, head Abbreviated Injury Scale of greater than or equal to 3, and riding a motorcycle, either as a driver or passenger, to be independent predictors of mortality. Subgroup analysis revealed being a motocross driver or passenger to be an independent predictor of improved survival (odds ratio [OR], 0.458; 95% confidence interval [CI], 0.359–0.585; p < 0.001 and OR, 0.127; CI 95%, 0.017–0.944; p = 0.044, respectively). Helmets were protective against mortality for all patients (OR, 0.866; 95% CI, 0.755–0.992; p = 0.039). CONCLUSION: Motocross and motorcycle collisions are distinct mechanisms of injury. Motocross riders are younger, more likely to wear protective devices, and less likely to use alcohol. Motocross collisions are associated with better outcomes compared with motorcycle collisions. Wearing a helmet is associated with improved survival for all riders. LEVEL OF EVIDENCE: Retrospective epidemiological study, level IV.